Hemodynamic stabilization in cesarean section patients administered spinal anesthesia: a quasi-experimental study comparing ephedrine and phenylephrine - Sindu Sintara; Annes Rindy Permana; Widigdo Rekso Negoro; Suryanto Suryanto; Reko Priyonggo; Muhammad Rodli (International Journal of Public Health Science (IJPHS), 2026)
This quasi-experimental research aimed to compare the effects observed following the administration of ephedrine 10 mg and phenylephrine 50 mg administered as therapeutic bolus doses for the management of intraoperative hypotension due to spinal anesthesia in cesarean section. The study involved 60 parturients who developed intraoperative hypotension during spinal anesthesia, who were divided into two groups treated with either phenylephrine or ephedrine. Maternal blood pressure, including systolic and diastolic values, was assessed pre- and post- vasopressor administration and analyzed using descriptive statistics, normality testing, and independent-samples t-tests. Both vasopressors were associated with increased maternal blood pressure following intervention, with no significant differences observed at baseline. However, between-group comparisons revealed statistically significant differences in post-intervention systolic and diastolic blood pressure (p < 0.05), indicating distinct hemodynamic response profiles. These findings demonstrate the effectiveness of both ephedrine and phenylephrine in treating hypotension associated with spinal anesthesia; vasopressor selection influences maternal blood pressure outcomes. From a practical perspective, this study provides clinically relevant evidence to inform anesthetic decision-making in maternal healthcare services, particularly in settings where therapeutic bolus administration is routinely utilized for the management of hypotension associated with spinal anesthesia.